Short-range magnetic behavior in manganites La0.93K0.07Mn1-xCuxO3 (0.0 ⩽ x ⩽ 0.09) above the Curie temperature. (11th February 2021) - Khammassi, Fatma; López, Jose F; Chérif, Wajdi; Mendoza, Aminta; Lanceros-Mendez, Senentxu; Dammak, Mohamed; Salazar, Daniel
Abstract: Manganites La0.93 K0.07 Mn1− x Cu x O3 ( 0.0 ⩽ x ⩽ 0.09 ), prepared by the solid state reaction method at high temperature, were studied structurally and magnetically. The unit cell parameters, as well as bond length d ( Mn, Cu)-O   Å and the bond angle θ ( Mn, Cu)- O 1 -Mn, were determined from the Rietveld refinement of the x-ray diffraction patterns. The Fourier-transform infrared spectroscopy analysis shows that Cu 2+ substitution induces variations in the vibration modes of the MnO6 octahedra. Magnetization vs. temperature M T at low magnetic field H=0 .01T were performed in the range 5 < T < 300 K under field coolingand zero field cooling conditions. All the samples exhibited a second-order paramagnetic–ferromagnetic (FM) transition at Curie temperature, T C, in the range between 199 and 285 K. The inverse susceptibility, χ − 1 ( T ) exhibits a linear Curie-Weiss (C-W) behavior for T > T CW *, while for T C < T < T CW *, it shows a deviation from the linear behavior predicted by the Heisenberg model. The mentioned deviation of χ − 1 T means that a short ferromagnetic state formation is present even for T > T C, which were characterized by the experimental effective magnetic moment, μ eff exp . A null spontaneous magnetization, m S, above T C was evaluated for all samples by using the Kouvel-Fisher method. This work evaluates the short-range FM clusters by means of an extension of the C-W approach to the T C < T < T CW * region, i.e., μ eff exp ( T ) = 2.3 C ( T ) μ B . Finally, the critical coefficient values, β and γ, showed that the 3D Heisenberg model fits adequately the x=0 .0 and x = 0.03 samples, while the 3D Ising model fits the x = 0.09 sample.